Challenges for sustainable biofuel industry development in Indonesia and Malaysia: A policy recommendation - Rianawati, E. (ETA-Florence Renewable Energies, 2021)
This research will talk about biodiesel specifically from palm oil processing waste, one of the forms of biofuels that will produce bioenergy, which has not only been looked upon globally but has been extensively studied by ASEAN and ASEAN countries, including Indonesia and Malaysia. These two countries are highly relevant to be talked about since they are the leading producer of palm oil and thus also the major producers of the potentially harmful-for-the-environment waste that could be utilized as biomass for biofuel production instead, hence benefited both countries in seizing the increasing global demand. In this research, the current outlook on Indonesia and Malaysiaâs POME sourced biofuel industry is being looked upon before identifying the challenges on multiple aspects that involve multiple key stakeholders. After finding those gaps or issues, general and country-specific policy recommendations that address the challenges are provided. Â© 2021, ETA-Florence Renewable Energies. All rights reserved.